A NEW APPROACH IN ECONOMICS: TRANSACTION COSTS THEORY - Iacobuta Andreea-Oana (Annals of the University of Oradea: Economic Science, 2009)
Ronald Coase article from 1937, The Nature of the Firm, meant a new way of thinking and conceiving of the world, especially of economic organisations. Coase argued that the firm and the market represent two alternative ways to organise the same transactio